Cadmium based II-VI Semiconducting Nanomaterials Synthesis Routes and Strategies - Majid, Abdul (Topics in Mining, Metallurgy and Materials Engineering,, 2018)
This book provides technological perspective and comprehensive overview on the research efforts related to II-VI group cadmium based semiconducting nanomaterials. It describes state-of-the-art information on different synthesis methods for preparation of these materials using a variety of experimental strategies. The effects of synthesis roots on structural, thermal, mechanical, lattice vibronic, electronic, optical and carrier transport characteristics of these nano-structures are systematically analyzed. A wide target readership comprising of students, researchers, scholars, scientists, technicians, academicians, industrialists can benefit from this book, as cadmium based semiconductors possess significant research and industrial interest thanks to their innovative properties.